Proceso atención de enfermería en paciente de 59 años de edad con fibrosis pulmonar. - Corrales Mora, Sanyi Nayely (2024)
Pulmonary fibrosis is a disease within the group of diffuse interstitial lung pathologies, whose cause is still unknown, and has an unfavorable prognosis with limited therapeutic options. Generally, it affects males over 50 years of age to a greater extent, manifesting with symptoms that progressively evolve such as difficulty breathing and dry cough. Currently, an increase in its recurrence is seen, due to improvements in diagnostic methods and the substantial increase in life expectancy. Mediators involved in its development have been named, which has allowed us to focus on them as possible therapeutic targets, leading to the development of medications formed from molecules such as Nintedanib and pirfenidone, which are considered the preferred treatment for individuals with pulmonary fibrosis with manifestations. acute or severe clinical conditions, given the promising prognoses obtained in clinical trials.